(untitled) (Zeitschrift für Migrationsforschung, 2023)
Der Beitrag fokussiert die Frage, wie Menschen, die in die Schweiz geflüchtet sind, mit den an sie herangetragenen Integrationsanforderungen umgehen. Auf der Basis von qualitativen Interviews rekonstruieren wir unterschiedliche Strategien im Umgang mit Herausforderungen der Arbeitsmarktintegration. »Flucht in die unbezahlte Arbeit« deuten wir sowohl als Eröffnung von Handlungsmöglichkeiten, um strukturell bedingten Hindernissen zu begegnen, als auch als Aneignung neoliberaler Selbstoptimierungsstrategien, zu denen sich die Personen gezwungen sehen. »Flight into Unpaid Work«? Labour Market Integration in Switzerland from the Perspective of Refugees In this contribution, we are pursuing the question of how people who have fled to Switzerland deal with the integration requirements they are confronted with. Based on qualitative interviews, we reconstruct different strategies in dealing with challenges concerning labour market integration. We interpret »flight into unpaid work« not only as the creation of opportunities for action to counter structurally conditioned obstacles, but also as an appropriation of neoliberal self-optimization strategies, to which the individuals feel forced.